2002
DOI: 10.2754/avb200271040517
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Morphological Evaluation of the Mucosa of Endometrium and Oviduct in Postpartum Goats

Abstract: The aim of this work was to characterize the structural changes in the surface epithelium and endometrial glands as well as oviduct mucosa in goats after parturition using the light and transmission electron microscopy. Fifteen Slovak short-haired goats were used. They were killed on days 3, 21, 36, and 40 after parturition. The evaluation of semithin sections from day 3 postpartum revealed impaired epithelial cells. Lymphocytes and neutrophil granulocytes were present in the lumen of uterine glands. Ciliated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…The range of values of its activity showed significant difference (P<0.001) between day 17 and day 34 of the evaluated period in the control group. Similar results were reported by Krajni~áková et al, (2002) in regressive changes occurring in the uterus during the postpartum period of goats. Zamiri et Blackshaw (1979) claim that alkaline phosphatase activity at the surface uterine glands of ewes gradually increased with peak values between day 14 and day 21 of the estral cycle.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The range of values of its activity showed significant difference (P<0.001) between day 17 and day 34 of the evaluated period in the control group. Similar results were reported by Krajni~áková et al, (2002) in regressive changes occurring in the uterus during the postpartum period of goats. Zamiri et Blackshaw (1979) claim that alkaline phosphatase activity at the surface uterine glands of ewes gradually increased with peak values between day 14 and day 21 of the estral cycle.…”
Section: Resultssupporting
confidence: 90%
“…Zamiri et Blackshaw (1979) claim that alkaline phosphatase activity at the surface uterine glands of ewes gradually increased with peak values between day 14 and day 21 of the estral cycle. The proliferation process of endometrial structures of sheep and goats as observed by Krajni~áková et al, (1999Krajni~áková et al, ( , 2002 is consistent with the occurrence of alkaline phosphatase activity and connected with their role in transformation mechanisms and metabolic processes occurring in the postpartum uterus. Statistical significance compared to day 17, 25 and 34 days after parturition ** = P<0.01; *** = P<0.001 Significance of differences between the control and experimental groups during the observed days after parturition a : a = P>0.05 ; b : b = P< 0.001 No significant statistical difference was noted (P>0.05) when evaluating alkaline phosphatase activity in the glandular cells of the endometrium (Tab.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were reported by Krajnicakova et al (2002) in regressive changes occurring in the NsE activity is given as the integrated absorbance in min/µm 3 of oviductal endothelial cells at a wavelength of 540 nm; *P < 0.05, **P < 0.01. Statistical significance compared between Day 17 and other days after parturition; b P < 0.001.…”
Section: Discussionsupporting
confidence: 86%
“…In healthy animals, the secretory activity of the oviduct decreases during the luteal phase and pregnancy, both of which are characterized by high progesterone levels (Nayak et al., 1976). In a study conducted in the oviduct of goats in the post‐partum period when the effect of the progesterone hormone disappears, it is reported that the number of secretory cells containing a large number of secretory granules in the ampulla epithelium increases from the post‐partum 21st day (Krajničáková et al., 2002). In another study examining the morphological features of the sheep oviduct in the post‐partum period, it is stated that the secretory cells in the early post‐partum period are light coloured and do not contain secretory granules.…”
Section: Introductionmentioning
confidence: 99%